Just watch me : a novel - Torenberg, Lior (Avid Reader Press, 2026)
Fleabag meets Big Swiss in this bold debut about a charismatic misfit who livestreams her life for seven days and nights to raise money to save her comatose sister--a poignant and darkly funny exploration of grief, forgiveness, and redemption. Dell Danvers is barely keeping it together. She's behind on rent for her studio apartment (formerly a walk-in closet), she's being plagued by perpetual stomach pain, and her younger sister, Daisy, is in a coma at a hospital that wants to pull the plug. Freshly unemployed and subsisting on selling plants to trust fund kids, Dell impulsively starts a 24-hour livestream under the username mademoiselle_dell to fundraise for private life support for Daisy. Dell is her stream's dungeon master, banishing those who don't abide by her terms and steadily rising up the platform's ranks with her sympathetic story and angry-funny screen presence. Once she discovers she has a talent for eating spicy food, her streaming fame explodes and her pepper consumption escalates from jalapeño to ghost to the hottest pepper on the Carolina Reaper. Dell is finally good at something--but as her behavior becomes riskier and a shadowy troll threatens to expose her dark past, Dell must reckon with what her digital life ignores, and what real redemption means. Narrated in seven taut chapters, one for each day of Dell's livestream, Just Watch Me careens through a week in the life of this charismatic misfit with a heart of gold. Voyeuristic and visceral, audacious and outrageous, Lior Torenberg's debut is both a razor-sharp tragicomedy about the internet economy and a surreptitiously moving tale about the desire to be watched, and the terror of being seen.